2018
DOI: 10.3390/vetsci5040090
|View full text |Cite
|
Sign up to set email alerts
|

Peer Feedback on Collaborative Learning Activities in Veterinary Education

Abstract: Collaborative learning activities are an increasingly prominent feature of veterinary curricula that have been redesigned to achieve competency-based graduate learning outcomes. This evolution challenges the traditional individualistic approach to veterinary education and necessitates revisions to assessment and feedback practices to ensure constructive alignment. Peer feedback has been widely reported in the medical education literature as a teaching intervention in collaborative learning settings, with learn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 86 publications
1
15
0
1
Order By: Relevance
“…Medical students are generally positive about peer assessment of professional behaviours [ 9 ], although the literature is mixed regarding student acceptance and satisfaction with peer assessment [ 11 ]. Papinczak et al [ 18 ] found students’ reported feeling uncomfortable carrying out peer assessment, while Dooley and Bamford [ 10 ] suggest that, for many students, the idea of directly evaluating one’s peers is at odds with traditional conceptualizations of the role of peers. It has been suggested that resistance to formative peer feedback is less common than summative peer assessment and student anxiety has been shown to decrease with time following early and repeated inclusion of peer assessment [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Medical students are generally positive about peer assessment of professional behaviours [ 9 ], although the literature is mixed regarding student acceptance and satisfaction with peer assessment [ 11 ]. Papinczak et al [ 18 ] found students’ reported feeling uncomfortable carrying out peer assessment, while Dooley and Bamford [ 10 ] suggest that, for many students, the idea of directly evaluating one’s peers is at odds with traditional conceptualizations of the role of peers. It has been suggested that resistance to formative peer feedback is less common than summative peer assessment and student anxiety has been shown to decrease with time following early and repeated inclusion of peer assessment [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…According to Hulsman et al [ 8 ] peer-assessment also reflects an ‘assessment-for-learning paradigm’ that is rooted within principles of social constructivist theories of learning. In many ways, the reported benefits of peer assessment in medical education mirror many of the key characteristics of Schon’s notion of the ‘reflective practitioner’, including that it may confer an improved ability to engage in self-reflective practice, develop greater self-awareness and increased critical reasoning skills [ 2 , 7 , 8 , 10 , 14 , 18 ].…”
Section: Introductionmentioning
confidence: 96%
See 3 more Smart Citations